THE BRISBANE 2000 TERMINOLOGY OF LIVER ANATOMY AND RESECTION - Steven M. Strasberg; J Belghiti; P.A. Clavien; Eldar Gadžijev; J.O. Garden; W.Y. Lau; M. Makuuchi; R.W. Strong (Zdravniški Vestnik, 2002)
Background. The Scientific Committee of the International Hepato-Pancreato-Biliary Association meeting in December 1998, created a Terminology Committee to deal with confusion in nomenclature of hepatic anatomy and liver resection. A terminology was sought which was anatomically correct, in which anatomical and surgical terms agreed, and which was consistent, self-explanatory, linguistically correct, translatable, precise and concise. Conclusions. After 18 months the International Committee presented a terminology that was accepted by the International Hepato-Pancreato-Biliary Association at the recent World Congress in Brisbane. The purpose of this paper is to present that terminology.